Stigma experiences of patients living with gastroparesis. Issue 4 (1st August 2021) - Taft, Tiffany H.; Craven, Meredith R.; Adler, Emerald P.; Simons, Madison; Nguyen, Linda
Abstract: Introduction: Stigmatization toward chronic digestive diseases is well documented. Patients perceive others hold negative stereotypes toward their disease and may internalize these beliefs as true. Because of this, stigmatization is associated with poor outcomes across disease‐related and psychosocial domains. No study to date evaluates stigmatization toward patients living with gastroparesis (GP), a poorly understood disease affecting gastric motility. We aimed to gain deep understanding of stigma in patients living with gastroparesis. Methods: Patients with GP were recruited from two university‐based gastroenterology practices as well as patient advocacy support groups. Participants underwent a semi‐structured qualitative interview about their experiences with stigma related to their GP diagnosis, which were audio‐recorded and transcribed to text for analysis using a grounded theory approach. Major themes with representative quotations were documented. Results: Twenty‐three patients participated. The majority were White, female, with idiopathic GP under the care of a gastroenterologist. All patients reported stigma related to GP. Seven major themes were found: stigma from healthcare providers, stigma within interpersonal relationships, GP as an invisible disease, blame, unsolicited suggestions on how to manage disease, disclosure, and stigma resistance. Conclusions: This is the first study to describe stigma experiences in patients with GP. The results suggest patients experience considerable stigmatization toward their condition from multiple sources. Patients also demonstrated resistance to negative beliefs, which can serve as a protective factor for the negative effects of disease stigma. Clinicians should be aware of stigma in GP patients, including their own potential internal biases and behaviors. Abstract :